(untitled) (Journal of the Bangladesh Society of Anaesthesiologists, 2014)
Background Post operative nausea and vomiting (PONV) is a common problem following general as well as regional anaesthesia. This causes great distress to the patient, may worsen surgical outcome and prolongs hospital stay. Prophylatic use of antiemetic in the preoperative or postoperative period reduces PONV. Objectives The study was designed to compare antiemetic effects of intravenous use of granisetron and ondansetron in the peroperative period for prevention of PONV following elective gynaecological surgery under general anaesthesia. Methods 60 (sixty) patients undergoing elective gynaecological surgery (total abdominal hysterectomy) under general anaesthesia of ASA grade I and II aged between 35-50 years were selected randomly and divided into two groups (group O & group G) of thirty patients each. Patients of group O received intravenous Inj, ondansetron 0.1 mg/kg body weight & group G received intravenous Inj. granisetron 2 mg bolus over 30 sec just before peritoneal closure. Both the group received a standard general anaesthesia. Postoperative analgesia was provided with diclofenac suppository (50mg) and ketorolac tromethamine 30mg intra-muscularly. In the recovery room occurrence of post operative nausea and vomiting was assessed for 12 hours. All data were compiled and analyzed for statistical significance by Students t tests (unpaired). P<0 .05 (CL 95%) was considered as significance. Results The incidence of post operative nausea and vomiting was reduced in both groups but no significant difference between the groups. No haemodynamic or psycho-mimetic adverse events were observed in the patients. DOI: http://dx.doi.org/10.3329/jbsa.v24i1.19795 Journal of Bangladesh Society of Anaesthesiologists 2011; 24(1): 18-22